2017
DOI: 10.7150/ijms.18623
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant AAV8-mediated intrastriatal gene delivery of CDNF protects rats against methamphetamine neurotoxicity

Abstract: Methamphetamine (METH) exerts significant neurotoxicity in experimental animals and humans when taken at high doses or abused chronically. Long-term abusers have decreased dopamine levels, and they are more likely to develop Parkinson's disease (PD). To date, few medications are available to treat the METH-induced damage of neurons. Glial cell line-derived neurotrophic factor (GDNF) has been previously shown to reduce the dopamine-depleting effects of neurotoxic doses of METH. However, the effect of cerebral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A reduction in apomorphine-induced rotational asymmetry and an increase in striatal DA levels were achieved by intranigral injection of adenoviral vector expressing GDNF (Ad-GDNF) at 10 weeks post 6-OHDA [27] or by intrastriatal injection of Ad-GDNF at 4 weeks post 6-OHDA [28]. Intrastriatal injection of adeno associated viral vector expressing CDNF (AAV8-CDNF) resulted in the reduction of apomorphine-induced rotational asymmetry and elevation of striatal DA levels at 5 weeks post 6-OHDA [29]. These studies also demonstrated that behavioral recovery is correlated with NTFs-induced trophic changes (restoration) of DA neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in apomorphine-induced rotational asymmetry and an increase in striatal DA levels were achieved by intranigral injection of adenoviral vector expressing GDNF (Ad-GDNF) at 10 weeks post 6-OHDA [27] or by intrastriatal injection of Ad-GDNF at 4 weeks post 6-OHDA [28]. Intrastriatal injection of adeno associated viral vector expressing CDNF (AAV8-CDNF) resulted in the reduction of apomorphine-induced rotational asymmetry and elevation of striatal DA levels at 5 weeks post 6-OHDA [29]. These studies also demonstrated that behavioral recovery is correlated with NTFs-induced trophic changes (restoration) of DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also demonstrated that behavioral recovery is correlated with NTFs-induced trophic changes (restoration) of DA neurons. The number of TH + cells in the SN and the density of TH + fibers in the STR were significantly increased after intrastriatal injection of an adenoviral vector expressing GDNF (Ad-GDNF) at 4 weeks post 6-OHDA [28] or of adeno associated viral vector expressing CDNF (AAV8-CDNF) at 5 weeks post 6-OHDA [29]. In contrast, results obtained from complete 6-OHDA lesioned rats indicated that GDNF infusion decreased apomorphine-induced rotation without nigrostriatal DA neuron recovery (neurorestoration) [30].…”
Section: Discussionmentioning
confidence: 99%
“…A flowchart of COMMAND is shown in Figure S4, along with examples of stereotaxic coordinates used by prior studies in Figure S5 (Aoi et al, 2000;Bilang-Bleuel et al, 1997;Cederfjä ll et al, 2015;Hattori et al, 1998;Horellou et al, 1994;Kilbourn et al, 1997;Kirik et al, 2000;Luo et al, 1999;Mandel et al, 1998;Rodrigues et al, 2003;Sacaan et al, 1991;Shults et al, 1996;Wang et al, 2017aWang et al, , 2017bZaczek et al, 1980).…”
Section: Star+methodsmentioning
confidence: 99%
“…CDNF, along with mesencephalic astrocyte-derived neurotrophic factor (MANF), is part of a recently discovered family of NTFs [ 16 ] that appear to be at least as potent as the well-studied GDNF against certain toxins [ 17 , 18 ], although acting via a distinct mechanism [ 19 ]. CDNF increases survival in a catecholaminergic cell line, PC12 cells, from cell death induced by either the DA neurotoxin 6-hydroxydopamine (6-OHDA) [ 20 , 21 ] or methamphetamine [ 22 ]. The NTF also protects DA neurons when administered prior to 6-OHDA in both rats [ 22 25 ] and nonhuman primates [ 18 ] or to MPTP-treated mice [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…CDNF increases survival in a catecholaminergic cell line, PC12 cells, from cell death induced by either the DA neurotoxin 6-hydroxydopamine (6-OHDA) [ 20 , 21 ] or methamphetamine [ 22 ]. The NTF also protects DA neurons when administered prior to 6-OHDA in both rats [ 22 25 ] and nonhuman primates [ 18 ] or to MPTP-treated mice [ 26 ].…”
Section: Introductionmentioning
confidence: 99%